REGIONAL IDENTITIES ALONG THE WEST BORDERS OF RUSSIA: THE ROLE OF HISTORY, POLITICS AND POSITIONAL BACKGROUNDS - Gritsenko, A.A. (Perm Federal Research Centre Journal, 2015)
The paper discusses the questions concerning exploring regional identities in Russia and especially in Russian western borderlands. It gives a short narrative about the author’s approach and methodological problems of studying regional identities along the Russian border. The deep interference of factors and backgrounds is illustrated on the results of the conducted research.